2017
DOI: 10.1111/josh.12537
|View full text |Cite
|
Sign up to set email alerts
|

Flavored Milk Consumers Drank More Milk and Had a Higher Prevalence of Meeting Calcium Recommendation Than Nonconsumers

Abstract: Consumption of flavored milk has the potential to increase milk consumption and reduce the percentage of children below the EAR for calcium; the percentage meeting AI for fiber was lower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
(81 reference statements)
3
11
0
Order By: Relevance
“…Overall, the results suggest that high school students are more likely to select, consume, and waste less fat‐free flavored milk, although milk waste was low across all milk options. These findings are consistent with other studies that have assessed milk consumption among grade school audiences in the United States 27,28 . Across school meal components, measuring levels of selection, consumption, and waste simultaneously provides data about what foods and beverages are available to select, which foods and beverages are selected, and how much is consumed and wasted.…”
Section: Implications For School Healthsupporting
confidence: 87%
“…Overall, the results suggest that high school students are more likely to select, consume, and waste less fat‐free flavored milk, although milk waste was low across all milk options. These findings are consistent with other studies that have assessed milk consumption among grade school audiences in the United States 27,28 . Across school meal components, measuring levels of selection, consumption, and waste simultaneously provides data about what foods and beverages are available to select, which foods and beverages are selected, and how much is consumed and wasted.…”
Section: Implications For School Healthsupporting
confidence: 87%
“…Some stakeholders worry that eliminating chocolate milk from schools will decrease students’ consumption of essential nutrients, such as calcium and vitamin D, and increase milk waste ( 13 – 16 ). Findings from a few studies validate these concerns ( 15 , 17 ). For example, one study in 11 Oregon elementary schools found that total milk sales decreased and milk waste increased after a chocolate milk removal policy was implemented ( 18 ), and research in 4 elementary and middle schools in an urban Massachusetts district found a significant increase in milk waste immediately after chocolate milk was removed from cafeterias ( 19 ).…”
Section: Introductionmentioning
confidence: 86%
“…Initiatives to eliminate flavoured milk in schools made no difference in added sugars consumption. However, there was a significant drop in overall milk and calcium consumption ( 114 , 115 ) because flavoured milk drinkers consumed more milk. Avoidance of flavoured milk may do little to address obesity and may reduce nutrient intake ( 112 , 113 ) .…”
Section: Questions About Foods Categorised As Ultra-processed Foods-novamentioning
confidence: 99%